Perinatal and social predictors of early childhood health in preterm infants: multicenter cohort study results - P. E. Khodkevich; O. S. Fedorova; K. V. Kulikova; I. A. Deev (Бюллетень сибирской медицины, 2025)
Aim. To identify perinatal and social predictors that determine the health of premature infants in early childhood, based on their birth weight. Materials and methods. This publication is part of a cohort prospective observational study of premature infants that was initiated in Tomsk in 2014 (Deev I.A., Kulikova K.V., Kobyakova O.S. et al., 2016). The main group consisted of 226 premature infants: 78 infants with low birth weight (LBW), 76 — very low birth weight (VLBW), and 72 – extremely low birth weight (ELBW), while a control group included 76 term infants. The follow-up period was 3 years, with examinations conducted every 12 months. Results. The study found that 57.1% (n = 36) of ELBW infants, 34.9% (n = 23) of VLBW infants, and 32.9% (n = 23) of LBW infants showed an “improvement” in their health during early childhood (transition from health groups IV and V to III, as well as transition from health group III to II at subsequent visits). The presence of siblings (for the main group OR = 2.6 [95% CI 1.3–5.3], p = 0.006, for children with ELBW OR = 8.4 [95% CI 1.0–69.6], p = 0.045) and the mother’s higher education (for children with VLBW OR = 3.9 [95% CI 1.2–12.2], p = 0.018 and with LBW OR = 3.4 [95% CI 1.2–9.9], p = 0.025) were identified as predictors of a favorable clinical prognosis. Perinatal and social predictors associated with the development of pathological abnormalities included intrauterine growth retardation, intraventricular hemorrhage, severe anemia in the neonatal period, maternal obesity, maternal smoking, parental age over 35 years, and lack of higher education for the mother. Conclusion. To implement a health-preserving strategy for the group of premature infants, especially those with ELBW, health improvement can be achieved by addressing controllable social factors.